2020
DOI: 10.1111/ddi.13043
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the distribution of a species‐rich group in a continental‐sized megadiverse country: Bats in Brazil

Abstract: Aim:The effective conservation and management of any given species frequently requires basic knowledge on its distribution, which is problematic for highly mobile, species-and ecologically-rich groups, like bats. Moreover, to produce detailed distributions for continental-sized, bat species-rich countries, like Brazil, is difficult, especially considering that ~60% of the country has not a single formal bat record. Using Species Distribution Modelling (SDM), we assessed the potential distribution of >100 speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 90 publications
(121 reference statements)
3
41
0
1
Order By: Relevance
“…, a pattern reflected in our study. Phyllostomidae bats are most commonly captured in the understory with mist nets, the country's most-used capturing method (Delgado-Jaramillo et al 2020). Families such as Molossidae and Vespertilionidae are also diverse, but they demand complementary methods to be registered (e.g., bioacoustics inventory), which is still rarely used in Brazil.…”
Section: Chiropteramentioning
confidence: 99%
“…, a pattern reflected in our study. Phyllostomidae bats are most commonly captured in the understory with mist nets, the country's most-used capturing method (Delgado-Jaramillo et al 2020). Families such as Molossidae and Vespertilionidae are also diverse, but they demand complementary methods to be registered (e.g., bioacoustics inventory), which is still rarely used in Brazil.…”
Section: Chiropteramentioning
confidence: 99%
“…For species with conspicuous vocalizations—like most bat families—the acoustical samplings we employed showed the potential to better refine SDMs in large and under-sampled regions, with relatively low sampling effort. This is quite useful in tropical areas, usually rich in bat species, but frequently understudied [ 55 , 56 ]. Using bioacoustics as a validation method, we also demonstrated that a careful decision on the modelling parameters and thresholds used is pivotal since, depending on the combination, they can produce very different outputs.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, this species was lumped with Lonchophylla bokermanni, but a morphological analysis revealed the existence of two species, with Atlantic Forest populations reassigned to Lonchophylla peracchii (Dias et al 2013, Cláudio et al 2018. This is the one of the Atlantic Forest endemic bat species, among Eptesicus taddeii, Histiotus alienus, Lasiurus ebenus and Myotis levis (Delgado-Jaramillo et al 2020). While Lonchophylla peracchii is classified as Least Concern by the IUCN (Solari 2017), it is considered as Data Deficient in the last assessment of the state of Espírito Santo fauna (Costa et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Bats play an important ecological role in their ecosystems, especially in pollination and seed dispersal, feeding on fruits, insects, nectar, and other vertebrates as well as blood (Fenton et al 1992). Of the 181 species recorded in Brazil (Delgado-Jaramillo et al 2020;Garbino et al 2020), 83 are known to occur in the state of Espírito Santo (Vela-Ulian et al in press).…”
Section: Introductionmentioning
confidence: 99%